2007
DOI: 10.1017/s1368980007226035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of economic inequality on chronic childhood undernutrition in Ghana

Abstract: Objective: Food insecurity and undernutrition remain particularly severe in developing countries where improvements in economic conditions have tended to benefit the advantaged groups and resulted in widespread inequalities in health. This study examined how economic inequality is associated with chronic childhood undernutrition. Design: A child was defined as chronically undernourished (stunted) if his or her height-for-age index was more than two standard deviations below the reference median. Household econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
88
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 29 publications
33
88
0
11
Order By: Relevance
“…We also showed that many of the dense households were similar in HWI to those in dispersed households. Recently asset-based indices as a measure of wealth have been shown to not only be a more reliable index of wealth under conditions of extreme poverty, but also to be related to health outcomes, including improved nutritional status 37,38 and reduced parasitic infections, 39,40 an observation consistent with our findings. In rural areas where income is inconsistent, asset-based indices are considered a valuable proxy for relative standard of living, which was of particular interest in our study area where wage work is extremely rare and variables such as number of wage earners or income would not capture household financial status.…”
Section: Discussionsupporting
confidence: 90%
“…We also showed that many of the dense households were similar in HWI to those in dispersed households. Recently asset-based indices as a measure of wealth have been shown to not only be a more reliable index of wealth under conditions of extreme poverty, but also to be related to health outcomes, including improved nutritional status 37,38 and reduced parasitic infections, 39,40 an observation consistent with our findings. In rural areas where income is inconsistent, asset-based indices are considered a valuable proxy for relative standard of living, which was of particular interest in our study area where wage work is extremely rare and variables such as number of wage earners or income would not capture household financial status.…”
Section: Discussionsupporting
confidence: 90%
“…Children of 4 and above birth order were more likely to be stunted than children of first birth order. This finding was in line with the study conducted In Cambodia [22], Nairobi Kenya [26], and Egypt [18]. This might be due to family unable to satisfy child dietary and other health care related services because of more number of children and might also be due to low awareness of family planning.…”
Section: Discussionsupporting
confidence: 88%
“…The magnitude of stunting in this study was higher than study conducted in Peru 26.6% [14], Brazil 29.9% [15], Sirlanka 11.8% [16], South Africa 20.2% [17] and Egypt 13.8% [18] and the national prevalence in EDHS 2006, 29.8% [10] and EDHS done in 2011, 32% [9]. However, the prevalence of stunting in the study was lower than study conducted in, Nepal 37% [19], India 51.6% [20], Lao PDR 40% [21], Cambodia 38.6% [22] also the study conducted in Democratic Republic of Congo 43.9% [23] ,Uganda 41.6% [24], Tanzania 44% [25], Kenya 40% [26], Sudan Khartoum 51% [27] and Ethiopia 42% [28]. This difference might be due to population migration from rural to urban in order to get better job and living condition, decreased purchasing power of the community, increment of food prices, inappropriate infant and young child feeding practices and child health care.…”
Section: Discussionmentioning
confidence: 90%
“…We surveyed the literature to determine the variables to include in our analysis. The variables selected included characteristics of the child, including age of the child (26,27) , sex of the child (20,28) , vaccination status (29) , size of the child at birth (20) and months of breast-feeding (30) . Additionally, facets of the child's mother and household are related to a child's risk for malnutrition; these included mother's education (19,31) , mother's age at first childbirth (21) , mother's BMI (32) , whether the mother has insurance, size of the household (33) , ethnicity and poverty (34)(35)(36) .…”
Section: Exposure Variablesmentioning
confidence: 99%